The Influence of Arab Spring on the Existence of Arabic Language Learning in the Multicultural Society of North Sulawesi - Oktavera, Hasnil (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This was a survey study which looked at the influence of Arab Spring phenomenon on the development of Arabic language learning in the multicultural society of North Sulawesi as well as its implications for the Arabic language learning model. The Arab Spring phenomenon that occurred from 2010 to 2011 that demanded a revolution in Arab countries reaped crucial impacts in various countries including Indonesia in terms of political, social, religious, cultural, and educational issues. The research method used the technique of proportionate stratified random sampling and involved 300 respondents from several regions in North Sulawesi Province based on three categories, namely areas that had a strong Muslim urban culture, areas that had a thick Islamic tradition, and areas that had Muslim minority issues. The results showed that the value of tcalculation > ttable (6.768 > 1.971). The foregoing demonstrated that Ho was rejected. Thus, it could be concluded that the Arab Spring had an effect on the existence of Arabic learning in the multicultural region of North Sulawesi in terms of interest and motivation. It also affected the content of Arabic teaching materials as well as the purpose and orientation of Arabic learning on the importance of Arabic as a language identity and Arabic as a communication language. Hence, the reconstruction of Arabic learning led to an increase in communication skills that contained local wisdom.Keywords: Arab Springs, Arabic Language Learning, Multicultural Society